Business Relationship Manager : Careers in IT Service Management - Brewster, Ernest (BCS guides to IT roles., 2014)
"Business relationship management (BRM) is central to all aspects of an organisation's interaction with existing and potential customers. It is crucial for building and maintaining strong relationships between service provider and customer and relies on understanding customer needs. It provides a mechanism for meeting those needs and identifies areas of required change and improvement. This highly accessible book gives an excellent introduction to the role of a BRM manager, covering areas such as purpose, required skills, responsibilities, interface and career progression as well as tools, standards and frameworks related to the role. It gives practical guidance to those new to the role or interested in getting a better understanding of what it entails."--